2(2p-3)=3(p+2)

Simple and best practice solution for 2(2p-3)=3(p+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2p-3)=3(p+2) equation:



2(2p-3)=3(p+2)
We move all terms to the left:
2(2p-3)-(3(p+2))=0
We multiply parentheses
4p-(3(p+2))-6=0
We calculate terms in parentheses: -(3(p+2)), so:
3(p+2)
We multiply parentheses
3p+6
Back to the equation:
-(3p+6)
We get rid of parentheses
4p-3p-6-6=0
We add all the numbers together, and all the variables
p-12=0
We move all terms containing p to the left, all other terms to the right
p=12

See similar equations:

| 5+3(w–4)=8 | | 175m-100m+52,250=55,275-200m | | I8-8(1-2x)-3=4-2x | | -15(22+11x)-13(12+23)=-22 | | 9y–13=14 | | (2y+5)(1-y)=0 | | -15=15+10(6+x) | | 1000x+50=450 | | 9x-9=8x+10 | | -4(x-4)-2x=-2(x-3)-2 | | 3(x-1)=5(2x-9) | | -15(22+11x)-(12+23x)=-22 | | 4(a-6)+12=36 | | 61=14-y | | 77=-13(13x-6)-(1-11x) | | 4m+5=32 | | −3/5(x−5)+4x=2/5x+12 | | 6.5+z=-8 | | 4x-14=-116-9x | | 180=x(1/3) | | 4−y=12 | | 2h+-7=7 | | -93=-2(x+5)-5(1-3x) | | 4/9=24/x;x=45 | | -3-13c=4 | | z+114=1 | | 12x=13+7x-7 | | 2(3x+2)+3(2x+3)+3=12x+16 | | 9(-9x+7)-8(-12-3)=-69 | | 3x/4-7=-4 | | 2(x-6)-12+4=4x-4 | | 6x-6/7=-x+2/2 |

Equations solver categories